1954
DOI: 10.1002/1097-4679(195407)10:3<272::aid-jclp2270100319>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Some factors influencing the unreliability of clinical judgments

Abstract: PROBLEMThe unreliability of clinical judgment is well known, particularly in the field of diagnosis(l1 8). Little has been done, however, toward any analysis of the factors responsible for this unreliability in order that it may be understood, controlled and corrected. Magaret ('I) points out that we need both a philosophy of diagnosis and a sophisticated understanding of its nature. Hunt, Wittson and Hunt (4* 6 , suggest that our understanding of clinical judgment might be furthered if we conceived of it, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

1956
1956
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 7 publications
0
26
1
Order By: Relevance
“…These results differ from those found in previous research, which showed that peer-ratings were as good in discriminating the level of social skill as trained judges' ratings of specific behavioral indices (Firth, Conger, Kuhlenschmidt, & Dorcey, 1986). In most studies reported, naive raters have served as raters because it was assumed that they approach to the scaled dimensions as taught, rather than to their intuition (Arnhoff, 1954;Cronbach, 1960). For the experiment, reported in Chapter 7, two changes are made.…”
Section: Research Implicationsmentioning
confidence: 77%
“…These results differ from those found in previous research, which showed that peer-ratings were as good in discriminating the level of social skill as trained judges' ratings of specific behavioral indices (Firth, Conger, Kuhlenschmidt, & Dorcey, 1986). In most studies reported, naive raters have served as raters because it was assumed that they approach to the scaled dimensions as taught, rather than to their intuition (Arnhoff, 1954;Cronbach, 1960). For the experiment, reported in Chapter 7, two changes are made.…”
Section: Research Implicationsmentioning
confidence: 77%
“…Arnhoff ( 2 ) found that inter-judge agreement on judging amount and kind of psychopathology decreased with amount of professional experience, although a repetition of Arnhoff's study(12), using revised instructions, reversed the results. Arnhoff ( 2 ) found that inter-judge agreement on judging amount and kind of psychopathology decreased with amount of professional experience, although a repetition of Arnhoff's study(12), using revised instructions, reversed the results.…”
Section: Problemmentioning
confidence: 90%
“…Although these techniques often lead to higher reliability (Bernardin & Beatty, 1984), there is no indication that they reduce the effects of differences of the immediate context for judgment. In previous research on clinical judgment, use of detailed descriptions of each category has met with little success in reducing contextual effects (Arnoff, 1954;Perrett, 1971); however, the results of Experiment 1 suggested circumstances under which anchoring might prove effective. Experiment 2 investigated these conditions using two different techniques for anchoring the scale of judgment.…”
mentioning
confidence: 84%
“…In experiments using clinical judgment, descriptive anchors have not succeeded in reducing contextual effects (Arnoff, 1954;Perrett, 1971). However, comparison between the results of Experiment 1 and Perrett's (1971) study suggested that providing scale anchors might reduce the effects of placing the target stimuli last for restricted-range conditions.…”
Section: Experiments 2: Anchoring the Scale Of Judgmentmentioning
confidence: 99%